1989
DOI: 10.1021/jm00126a013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro acetylcholine-storage-blocking activities, and biological properties of derivatives and analogs of trans-2-(4-phenylpiperidino)cyclohexanol (vesamicol)

Abstract: Eighty-four analogues and derivatives of the acetylcholine-storage-blocking drug trans-2-(4-phenylpiperidino)-cyclohexanol (vesamicol) were synthesized, and their potencies were evaluated with the acetylcholine active-transport assay utilizing purified synaptic vesicles from Torpedo electric organ. The parent drug exhibits enantioselectivity, with (-)-vesamicol being 25-fold more potent than (+)-vesamicol. The atomic structure and absolute configuration of (+)-vesamicol were determined by X-ray crystallography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(110 citation statements)
references
References 2 publications
3
106
0
Order By: Relevance
“…The bromo substituent of OBDV was replaced by a trimethylstannyl group by the reaction of Pd(PPh 3 ) 4 and hexamethylditin to obtain the corresponding precursor, o-trimethylstannyltrans-decalinvesamicol (OTDV), for the radiosynthesis of [ 77 Br]OBDV, with an yield of 65% (Kozaka et al, 2012). DV was prepared according to Roger's protocol (Rogers et al, 1989). During the purification of [ 77 Br]OBDV with HPLC, no UV peak of OBDV was detected because the concentration of OBDV was less than the detection limit.…”
Section: Materials and Methods Synthesis Of Obdv And Otdvmentioning
confidence: 99%
See 1 more Smart Citation
“…The bromo substituent of OBDV was replaced by a trimethylstannyl group by the reaction of Pd(PPh 3 ) 4 and hexamethylditin to obtain the corresponding precursor, o-trimethylstannyltrans-decalinvesamicol (OTDV), for the radiosynthesis of [ 77 Br]OBDV, with an yield of 65% (Kozaka et al, 2012). DV was prepared according to Roger's protocol (Rogers et al, 1989). During the purification of [ 77 Br]OBDV with HPLC, no UV peak of OBDV was detected because the concentration of OBDV was less than the detection limit.…”
Section: Materials and Methods Synthesis Of Obdv And Otdvmentioning
confidence: 99%
“…In 1989, Rogers et al reported that trans-decalinvesamicol (DV) revealed high affinity for VAChT among various vesamicol analogues in in vitro and in vivo binding assays ( Fig. 1) (Rogers et al, 1989). On the basis of the observations of DV and (-)-oIV, we synthesized o-bromo-trans-decalinvesamicol (OBDV) and o-iodo-trans-decalinvesamicol (OIDV) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of cardiac norepinephrine spillover to plasma, the difference between release and reuptake, relies on the determination of the norepinephrine concentration difference between the coronary sinus and the arterial system, fractional extraction of tritium-labeled norepinephrine, and coronary sinus blood flow [63,64]. Increased [183,233] p-(lSF)fluorobenzylguanidine [189] 11C-benzovesamicol [191] nC-CGP 12177 [196][197][198] nC-carazolol [199,200] 11C-prazosin [201] 11C-MQNB [202][203][204][205][206] N-(~SF)fluoroethyl-( -)-QNB [207] 11C-PKl1195 [211] 123I-m-iodobenzylguanidine (12~I-MIBG) [69][70][71][72][73][74][75] l~I-iodocyanopindolol (I~I-ICYP) [153][154][155][156] (1~ I)N-methyl-4-iododexetimide [164] cardiac norepinephrine spillover to plasma has been demonstrated using this technique in patients with essential hypertension [65], ventricular arrhythmias [66], myocardial ischemia [67], and congestive heart failure [29,68].…”
Section: First Applications Of Radiotracers Under Experimental Conditmentioning
confidence: 99%
“…However, on the outer membrane surface of the ACh storage vesicles, a specific binding site could be characterized using vesamicol, a compound originally designed as an analgetic. High-affinity binding of vesamicol to synaptic vesicles of parasympathetic nerve cells was demonstrated [191]. Tritiated vesamicol and 5-(125I)iodobenzovesamicol were first studied in mice and rats.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…This classical method has a number of limitations, such as the requirement of an excess of inorganic base, longer reaction times, low nucleophilicity in the case of deactivated aromatic amines, and in some cases low boiling points when elevated temperature is necessary (7). Even though some of these drawbacks have been overcome with the use of a variety of catalysts, such as Bi(OTf) 3 (8), InBr 3 (9), Cu(BF 4 ) 4 O (19), there are still many limitations, such as the formation of bisalkylated products, longer reaction times (8,9,11Á18), stoichiometric amounts of catalysts (9,12,14Á16,19), and harsh reaction conditions (15,18). However, some of these reported methods are not applicable for aliphatic amines (8,9,11Á14,17).…”
mentioning
confidence: 99%